FROM REVIEW TO REFLECTION: EXPLORING STUDENTS’ PERSPECTIVES ON CRITIQUING ACADEMIC ARTICLES - Muhammad Arif Sanjaya (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study investigates perceptions of, attitudes toward, challenges in, and how critique is influencing students’ academic and reflective growth. Data were collected according to a mixed-methods study design through questionnaires and semi-structured interviews with 25 undergraduate students enrolled in a Critical Reading course at Universitas Samudra. It has been found that appreciation by the students of the significance of critique in building critical thinking, analytical reasoning, and academic writing exists, but they find it challenging to handle complex terminologies, identifying arguments, and being objective. Time also seems to be a limiting factor. Students perceive that guided practice, group discussion, and further practice would make them more competent in critiquing. The literature addresses the need for learning processes that enable students to transition from recapitulation to critical thinking, and eventually to more intellectual engagement and confidence in scholarship. The literature guides the overarching argument about critical reading and its role in college learning.